Smart Public Decision-Making Model In The Era Of Big Data - Han, XiaoXia (IJRDO - Journal of Social Science and Humanities Research, 2016)
We are now moving toward a new era ——Big Data Era,which is completely different from the past. As a important strategic resource in the big data era ,the big data is causing huge change not only in the economic sphere but also in the whole society,including the social governance. In the era of big data The mode of policy making should convert form the original small-scale digital management which relies on the intuition and past experience to the Smart Public Decision Making which based on the analysis of big data ,fully making use of the big data technology and tremendous amount of information behind the data , so as to enhance the scientificity and effectiveness of policy making ,realizing the modernization and innovation of government governance. On the basis of big data technology this paper expatiates the meaning and characteristics of intelligent decision making, discusses the operation mode of intelligent decision making is discussed. Furthermore in order to further develop the power of the public, proposes to apply the crowdsouring into the smart decision-making mode so as to improve the scientific 、 democracy and effectiveness of public decision-making.